Principles of Macroeconomics : Activist vs. Austerity Policies - Sherman, Howard J.; Meeropol, Michael A.; Sherman, Paul D.; Taylor and Francis (Boca Raton, FL : Taylor and Francis, an imprint of Routledge, 2018)
In the years since 2007 the U.S. economy has endured a severe financial crisis, a Great Recession, and continuing heavy unemployment. These events have led to increasing discontent among many people contributing to a substantial vote for Bernie Sanders and the election of Donald Trump. Meanwhile, Europe has witnessed the rise of nationalist parties and Brexit. In the face of these problems and events, economics must change.Principles of Macroeconomics: Activist vs. Austerity Policies provides an antidote to the standard macro texts offering multiple points of view instead of one standard line, a fact-based focus on the causes and cures of instability in economics, and an examination of inequality in the United States.Readers are introduced to both the Classical view, which takes the conservative approach and argues for an austerity program to reduce the size of the government; and the Progressive view, which argues for government intervention to create a strong recovery. These ideas are applied to all the key macroeconomic topics including economic growth, business cycles, and monetary policy. Using the methodology of Wesley Mitchell and drawing on the work of Keynes, the authors also explore topics such as unemployment, the human cost of economic crashes, increasing inequality of income, and the history of capitalism. This second edition includes new material on the Obama recovery, the crisis in the Eurozone, the rise of populism, and the current state of healthcare, education, and environmental issues in America to bring the text fully up to date. It will be of great interest to undergraduate students and particularly those studying the economics of the United States.
List of Figures, List of Tables,--Preface, Acknowledgments. --Part 1. Basic Issues of Macroeconomics. --Chapter 1 What is Macroeconomics? Chapter 2 Evolution of Capitalism. Chapter 3 The Classical View of the Macroeconomy. Chapter 4 The Keynesian Revolution. Chapter 5 National Income Accounting. Chapter 6 Classical and Keynesian Graphical Analysis. Chapter 7 Introduction to Economic Growth. Chapter 8 Introduction to Business Cycles. --Part 2. Growth and Instability. --Chapter 9 Investment and Profit. Chapter 10 The Multiplier. Chapter 11 Employee Income and Profit. Chapter 12 Consumer Spending. Chapter 13 Credit and Interest. Chapter 14 Housing Bubble and Financial Crisis. Chapter 15 Government Spending, Taxes, and Deficits. Chapter 16 The Trade Gap. Chapter 17 Business Cycles.Chapter 18 The Obama Recovery: 20092016. --Part 3. The Global Macroeconomy.-- Chapter 19 Globalization and the Spread of Instability. Chapter 20 The Eurozone and Currency Issues. --Part 4. Finance and Monetary Policy. --Chapter 21 Inflation. Chapter 22 Monetary Policy and Financial Regulation. Chapter 23 Debates over Monetary Policy.--Part 5. Fiscal Policy and Full Employment.--Chapter 24 Fiscal Policy: How to Stimulate an Economy. Chapter 25 Fiscal Policy: Austerians and Deficit Hawks vs. Stimulus. Chapter 26 A Road to Full Employment. Bibliography.-- Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: BUSINESS & ECONOMICS / Economics / Macroeconomics; Macroeconomics; Capitalism; Fiscal policy; Macroeconomics -- United States; Capitalism -- United States; Fiscal policy -- United States; Electronic books